Scale Up Sourcebook - Cooley, Larry; Howard, Julie (Purdue University, 2019)
The Scale Up Sourcebook is informed and inspired by the September 2018 conference, Innovations in Agriculture: Scaling Up to Reach Millions, organized by Purdue University, in partnership with the African Devel opment Bank. The Sourcebook consolidates, extends, and disseminates so me of the scaling insights presented at the Purdue conference. It is i ntended as an easy-to-use guidebook targeted to a broad and diverse au dience of stakeholders associated with scaling agricultural technologi es and innovations to meet the needs of the world’s poor. The Sourcebo ok has nine chapters: designing with scale in mind; assessing scalabil ity; using commercial markets to drive scaling; financing the transiti on to scale; creating an enabling environment for scale; tailoring met rics, monitoring, and evaluation to support sustainable outcomes at sc ale; and the critical role of intermediary and donor organizations. Th e Sourcebook provides guidance, tips, and examples, along with links a nd references to additional resources on scale up.